Electrical impedance to easily discover undeclared freeze-thaw cycles in slaughtered bovine meat - Dell’Osa A. H.; Battacone G.; Pulina G.; Fois A.; Tocco F.; Loviselli A.; Concu A.; Velluzzi F. (Journal of Electrical Bioimpedance, 2021)
A portable electrical impedance spectroscopy device was developed to monitor the bioimpedance resistive component of bovine meat by injecting a sinusoidal current of 1 mA at 65 kHz. Both right and left longissimus dorsi muscles were trimmed from 4 slaughtered cows. The left muscle portions were frozen to −18 °C for 7 days while the right ones were meantime maintained at 5 °C. Mean value of impedance per length (Ω/cm) of frozen and thawed left samples was 31% lower than that of right non-frozen one (P = 0.0001). It was concluded that the device is reliable for monitoring the maturation of beef meat in situ with the possibility of revealing undeclared freeze-thaw cycles.